METODE KONSTRUKSI UNTUK MENYELESAIKAN MASALAH TATA LETAK FASILITAS - Kusumah, Yaya Sukjaya (Jurnal Pengajaran MIPA, 2001)
The facility layout design problem is concerned with determining the location of a number of facilities which optimises a prescribed objective such as profit, cost, or distance. This problem arises in many applications; for example, in design of buildings and in plant layout design. Most approaches for solving this problem are heuristic in nature and based on graph theoretic concepts. Graph theoretically, when the objective is to maximize profit, the facility layout design problem is to determine, in a given edge weighted graph G, a maximum weight planar sub graph. In this paper, a new heuristic based on graph theoretic concepts is presented. A comparative analysis based on 3600 random test problems demonstrates the value of this algorithm.